2020
DOI: 10.1016/j.ekir.2020.02.1028
|View full text |Cite
|
Sign up to set email alerts
|

Current Management of Hyperkalemia in Patients on Dialysis

Abstract: Patients with end-stage renal disease (ESRD) on maintenance dialysis have a high risk of developing hyperkalemia, generally defined as serum potassium (K þ) concentrations of >5.0 mmol/l, particularly those undergoing maintenance hemodialysis. Currently, the key approaches to the management of hyperkalemia in patients with ESRD are dialysis, dietary K þ restriction, and avoidance of medications that increase hyperkalemia risk. In this review, we highlight the issues and challenges associated with effective man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 83 publications
(126 reference statements)
0
57
0
1
Order By: Relevance
“…Hyperkalemia in dialysis patients can reach figures of up to 37% of patients, increasing the potential risk of sudden death in the interdialytic period. 24 In a metaanalysis that evaluated observational studies, having hyperkalemia increased the risk of cardiac mortality by 1.4 times. 25 About 11% of the patients had 25-OH vitamin D <20 ng/mL, indicating that the vast majority of patients have an adequate serum level of this vitamin.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkalemia in dialysis patients can reach figures of up to 37% of patients, increasing the potential risk of sudden death in the interdialytic period. 24 In a metaanalysis that evaluated observational studies, having hyperkalemia increased the risk of cardiac mortality by 1.4 times. 25 About 11% of the patients had 25-OH vitamin D <20 ng/mL, indicating that the vast majority of patients have an adequate serum level of this vitamin.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of low-K 1 dialysate (,2.0 mmol/L) has been a focus of concern as the rapid lowering of K 1 during dialysis may potentially provoke cardiac arrhythmias and cardiac mortality. 6,39,40 A prospective multicenter study found that patients with a high predialysis serum K 1 concentration ($5 mmol/L) prescribed a dialysate K 1 concentration of 1 mmol/L were at higher risk of mortality than patients prescribed 2 mmol/L or 3 mmol/L dialysate. 41 In a large-scale global study, no clinically meaningful difference in mortality or arrhythmias was detected among patients on 3.0 mmol/L or 2.0 mmol/L dialysate at any level of predialysis serum K 1 .…”
Section: Rationale For the Treatment Of Hyperkalemia In Patients Receiving Maintenance Hemodialysismentioning
confidence: 99%
“…Hyperkalemia is associated with increased risk of arrhythmias and cardiac arrest and is prevalent in patients undergoing hemodialysis. 6 However, there is limited evidence on how best to manage these risks. Even at the initial stages of hyperkalemia management, there are no clear guidelines on what level of K 1 constitutes a concern, specifically in patients receiving maintenance hemodialysis, and what frequency of monitoring would most meaningfully capture fluctuations in patient serum K 1 .…”
Section: Gaps In the Evidence Base And Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations